Bank bailouts, international linkages and cooperation - Friederike Niepmann; Tim Schmidt-Eisenlohr (Center for Economic Studies and ifo Institute (CESifo), 2011)
Financial institutions are increasingly linked internationally. As a result, financial crisis and government intervention have stronger effects beyond borders. We provide a model of international contagion allowing for bank bailouts. While a social planner trades off tax distortions, liquidation losses and intra- and inter-country income inequality, in the non-cooperative game between governments there are inefficiencies due to externalities, no burden sharing and free-riding. We show that, in absence of cooperation, stronger interbank linkages make government interests diverge, whereas cross-border asset holdings tend to align them. We analyze different forms of cooperation and their effects on global and national welfare.
Keywords: F36; F42; G01; G28; 330; bailout; contagion; financial crisis; international institutional arrangements; Finanzmarktkrise; Bankenkrise; Schuldenübernahme; Ansteckungseffekt; Internationale wirtschaftspolitische Koordination